ANALISIS KESESUAIAN TEKS VERBAL DAN VISUAL PADA BUKU TEKS BAHASA INDONESIA KELAS X PENERBIT KEMENTERIAN PENDIDIKAN DAN KEBUDAYAAN RI EDISI REVISI 2017 - Muhamad Irwan Saputra (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2019)
ABSTRACT This study aims to describe the analysis of verbal and visual text in the books of class X students at SMA Negeri 1 Secanggang and measure the level of students' understanding of verbal and visual texts and their analysis. This study uses qualitative interpretatif and quantitative data. The study was taken by interview, observation and questionnaire. From the results of the analysis, it can be seen that, (1) Halliday's transitivity concept analysis shows the verbal text on the process type component the number of occurrences of verbal text 11 times, on the participant component the number of appearances on verbal text is 11 times, and on the circumstance component the number of appearances on verbal text is 8 times. (2) Analysis of visual text in class X students' books using a multimodal analysis model by Kres s and Van Leeuwen which includes linguistic, visual, audio, gestural, and location analysis . (3) Analysis of the suitability of verbal and visual texts shows that the highest amount of conformity is in the display text of the exposition of "Drug Danger for Young Generation" and the display of the negotiation text "Bidding Letter", while for the least amount of conformity is in the debate text "Do Cell phones Dangerous? " And the text of the poem "My Cushion is My Blanket in the Wind" . (4) Usefulness text analysis of verbal and visual to teaching materials are detailed as follows : needs analysis on all teachers Indonesian (100%) and the rest of the student group limited field answered that require additional reading materials such as text analysis verbal and visual , feasibility analysis validation of subject matter experts on the assessment of the feasibility aspect of the contents declared "Very Good" with an average total percentage of 83.59%, the feasibility aspect of the presentation of "Very Good" with a total percentage of 91.25%, the feasibility aspect of language "Very Good "With an average percentage of 82.14%. The validation results from the design experts showed that the average percentage of all sub-components of the assessment of the feasibility of the design of reading material 89.58% with the criteria "Very Good" . Analysis of the results of responses obtained from teachers on average 97.22% with the criteria "Very Good" and students an average of 83.47% with the criteria "Very Good". Thus, this product is declared suitable for use as additional reading material for students and teachers. This research has implications that can be used by teachers and students as a companion to the learning process and improve the critical thinking of teachers and students.  Keywords: analysis, multimodal, transitivity, verbal text, visual text